Designing nahshorna bilingual media for nahwu-shorof basic learning - Iin Baroroh Ma'arif; Akhmad Kanzul Fikri; Atik Husna (Universitas Islam Malang, 2020)
This study is conducted on the basis of researcher’s observation that students are lack of interest of study in learning Arabic grammar, namely Nahwu-Shorof basic learning. Students have good basic on English ability. The objective of this study is to find out the feasibility of designing ‘’NahShorNa’’ bilingual media for Nahwu-Shorof basic learning for students. This study involved 12 students. The subjects of this study are second grade students of An-Nashriyah Islamic Boarding School. This study used qualitative data and used Research and Development (R&D) Research Design. The instruments of this study used observation, interview, questionnaire and documentation. The study focused on reading ability. The findings of the study that are the result of media validation is 88% score in very good category, the result of two materials validation is interesting categories, English material is 75% score in pretty good category, the Arabic material is 73,75 % score in pretty good category and the result of user validation in preliminary field study is ‘’Good’’ response